Genetic diversity and population structure in Nothofagus pumilio, a foundation species of Patagonian forests: defining priority conservation areas and management - Mattera, María Gabriela; Pastorino, Mario Juan; Lantschner, Maria Victoria; Marchelli, Paula; Soliani, Carolina (Springer Nature, 2020)
Patagonian forests are the southernmost temperate forests in the world, and Nothofagus pumilio is one of their most ecologically important tree species (i.e., a foundation species). It presents great adaptability and a wide distribution range, making it a suitable model for predicting the performance of trees facing global climate change. N. pumilio forests are increasingly threatened by extreme climatic events and anthropogenic activities. This study aims to identify priority conservation areas and Genetic Zones (GZs) for N. pumilio, promoting the implementation of specific practices to ensure its management and long-term preservation. Thirty-five populations (965 trees) sampled across its distribution (more than 2200 km latitudinally) were genotyped with SSRs, and geographical patterns of genetic variation were identified using Bayesian approaches. The phylogeographic patterns of the species and geomorphological history of the region were also considered. Six priority conservation areas were identified, which hold high allelic richness and/or exclusive allelic variants. Eighteen GZs were delineated based on the genetic structure of this species, and maps showing their distributional range were drawn up. Overall, this study defines management units based on genetic data for N. pumilio for the first time, which will facilitate the establishment of sustainable practices and highlight priorities for investment of conservation funding.